Answer:
y = 3(x + 1)² - 7
Explanation:
y = 3x² + 6x - 4
First, factor out the coefficient of the quadratic eq'n:
y = 3(x² + 2x - ⁴/₃)
Use the "complete the square" rule;
The "x² + 2x" should be rewritten as "(x + 1)² - 1", i.e. place into squared brackets x (without the power 2) and add half the coefficient of the x-term, you then need to subtract the square of the constant term in the squared brackets and then simplify:
y = 3((x + 1)² - 1 - ⁴/₃)
y = 3((x + 1)² - ⁷/₃)
Finally, multiply the 2 terms you end up with by the 3, factored out initially:
y = 3(x + 1)² - 7